Further Result on Passivity for Discrete-Time Stochastic T-S Fuzzy Systems with Time-Varying Delays - Ting Lei; Qiankun Song; Zhenjiang Zhao (Discrete Dynamics in Nature and Society)
The passivity for discrete-time stochastic T-S fuzzy systems with time-varying delays is investigated. By constructing appropriate Lyapunov-Krasovskii functionals and employing stochastic analysis method and matrix inequality technique, a delay-dependent criterion to ensure the passivity for the considered T-S fuzzy systems is established in terms of linear matrix inequalities (LMIs) that can be easily checked by using the standard numerical software. An example is given to show the effectiveness of the obtained result.